The Influence of Work Safety, Compensation, and Work Facilities on Employee Performance at PT. Sea Asih Lines - Asta, Septilia Diva; Pohan, Yuli Arnida (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Human resources are people who provide energy, thoughts, talents, creativity and efforts to the company. Human resources (HR) in the company need to be managed professionally in order to achieve a balance between the needs of employees and the capabilities of the company's organization. This research was conducted at PT. Sea Asih Lines located at Jalan Bangka Belawan No. II. Medan, Belawan City, Medan City, North Sumatra 20411. The planned research period is March 2025 to August 2025. In this study, the population is all employees of PT. Sea Asih Lines, totaling 80 people. Saturated sampling is a sampling technique when all members of the population are sampled. In this study, the sample taken is all employees who are the target of the study, totaling 80 employees. Based on the results of the study, work safety partially does not have a positive and significant effect on employee performance. Compensation partially has a positive and significant effect on employee performance. Work facilities partially have a positive and significant effect on employee performance. There is a simultaneous or joint influence between work safety, compensation, and facilities on employee performance.